KAJIAN BENTUK, FUNGSI, MAKNA DAN WARNA MOTIF SONGKET TEBO, JAMBI - Fitriza Emilda, Drs. Efrizal, M.Pd., Dra. Lisa Widiarti, M.Sn. (Universitas Negeri Padang, 2018)
This study aims to describe the shape of the product, the variety of motives, functions, meanings and colors of Tebo songket whose information is not widely known to the wider community. The method used to collect data is the method of observation, documentation and interviews. The results of the study show that there are 5 types of songket Tebo products in the form of gloves, scarves, headbands, wallets and wall hangings. Tebo Songket has 6 motifs, namely Tapak Kudo, Bungo Tanjung, Bungo Mawar, Kajang Lako, Konde Minah and Tanggo Rajo motifs. The function of Tebo songket is in the form of function and ornamental function. Songket Tebo cloth is usually used on official / custom events. The meaning of Tebo songket motif is taken from the history and culture of the Tebo region. Tebo Songket has various colors such as Red, Pink, Blue, Light Blue, Purple, Gray, Black and White.Keywords: Songket Tebo, Jambi.